Proof of Concept: Game-Based Mobile Learning—The First Experience With the App Actionbound as Case-Based Geocaching in Education of Veterinary Neurology - Nessler, Jasmin; Schaper, Elisabeth; Tipold, Andrea (Frontiers in Veterinary Science, 2021)
Case-based learning is a valuable tool to impart various problem-solving skills in veterinary education and stimulate active learning. Students can solve imaginary cases without the need for contact with real patients. Case-based teaching can be well performed as asynchronous remote-online class. In time of COVID-19-pandemic, many courses in veterinary education are provided online. Therefore students report certain fatigue when it comes to desk-based online-learning. The app “Actionbound” provides a platform to design digitally interactive scavenger hunts based on Global Positioning System (GPS) - called “bounds”- in which the teacher can create a case study with an authentic patient via narrative elements. This app was designed for multimedia-guided museum or city tours initially. The app offers the opportunity to send the students to different geographic localizations for example in a park or locations on the University campus, like geocaching. In this way, students can walk outdoors while solving the case study. The present article describes the first experience with Actionbound as a tool for mobile game-based and case-orientated learning in veterinary education. Three veterinary neurology cases were designed as bounds for undergraduate students. In the summer term 2020, 42 students from the second to the fourth year of the University of Veterinary Medicine Hannover worked on these three cases, which were solved 88 times in total: Case 1 and 2 were each played 30 times, case 3 was played 28 times. 47 bounds were solved from students walking through the forest with GPS and 41 were managed indoors. After each bound students evaluated the app and the course via a 6-point numerical Likert rating scale (1=excellent to 6= unsatisfactory). Students playing the bounds outdoors performed significantly better than students solving the corresponding bound at home in two of the three cases (p=0.01). The large majority of the students rated the course as excellent to good (median 1.35, range 1-4) and would recommend the course to friends (median 1.26, range 1-3). Summarizing, in teaching veterinary neurology Actionbound´s game-based character in the context of outdoor activity motivates students, might improve learning, and is highly suitable for case-based learning.